Transformative Kiai Leadership and the Formation of Entrepreneurial Culture in Pesantren - Bambang Wiratmuko; Ahmad Tanzeh; Nur Efendi; Liatul Rohmah (Lembaga Penelitian, Penerbitan dan Pengabdian Masyarakat (LP3M) IAI Al Urwatul Wutsqo - Jombang, 2026)
This study examines the leadership of kiai in shaping the entrepreneurial culture of santri at Qur’any Islamic Boarding School in Blitar and Fathul Ulum Islamic Boarding School in Jombang. The research was motivated by the growing need for Islamic educational institutions to strengthen students’ economic independence while maintaining spiritual and moral values. This study employed a qualitative approach with a multi-site design. Data were collected through in-depth interviews, participant observation, and documentation studies involving kiai, pesantren administrators, teachers, and santri. Data analysis was conducted through data condensation, data display, and conclusion drawing using single-site and cross-site analysis techniques. The findings reveal that kiai leadership plays a transformative role in fostering an entrepreneurial culture through exemplary leadership, internalisation of spiritual values, participatory engagement, and collective habituation. Entrepreneurial activities in both pesantrens were integrated with Islamic values such as sincerity, discipline, responsibility, and social empowerment. The kiai functioned not only as a religious leader but also as an agent of socio-economic transformation, encouraging santri to develop independence and productive skills. This study contributes to the development of Islamic educational leadership theory by proposing a spiritually based transformational leadership perspective within pesantren entrepreneurship education. The findings also demonstrate that pesantren can function as institutions of community empowerment capable of integrating spirituality, character education, and economic productivity within a holistic Islamic educational framework